Vanillic Acid Restores Coenzyme Q Biosynthesis and ATP Production in Human Cells Lacking COQ6. (10th July 2019) - Acosta Lopez, Manuel J.; Trevisson, Eva; Canton, Marcella; Vazquez-Fonseca, Luis; Morbidoni, Valeria; Baschiera, Elisa; Frasson, Chiara; Pelosi, Ludovic; Rascalou, Bérengère; Desbats, Maria Andrea; Alcázar-Fabra, María; Ríos, José Julián; et al.
Abstract : Coenzyme Q (CoQ), a redox-active lipid, is comprised of a quinone group and a polyisoprenoid tail. It is an electron carrier in the mitochondrial respiratory chain, a cofactor of other mitochondrial dehydrogenases, and an essential antioxidant. CoQ requires a large set of enzymes for its biosynthesis; mutations in genes encoding these proteins cause primary CoQ deficiency, a clinically and genetically heterogeneous group of diseases. Patients with CoQ deficiency often respond to oral CoQ10 supplementation. Treatment is however problematic because of the low bioavailability of CoQ10 and the poor tissue delivery. In recent years, bypass therapy using analogues of the precursor of the aromatic ring of CoQ has been proposed as a promising alternative. We have previously shown using a yeast model that vanillic acid (VA) can bypass mutations of COQ6, a monooxygenase required for the hydroxylation of the C5 carbon of the ring. In this work, we have generated a human cell line lacking functional COQ6 using CRISPR/Cas9 technology. We show that these cells cannot synthesize CoQ and display severe ATP deficiency. Treatment with VA can recover CoQ biosynthesis and ATP production. Moreover, these cells display increased ROS production, which is only partially corrected by exogenous CoQ, while VA restores ROS to normal levels. Furthermore, we show that these cells accumulate 3-decaprenyl-1, 4-benzoquinone, suggesting that in mammals, the decarboxylation and C1 hydroxylation reactions occur before or independently of the C5 hydroxylation. Finally, we show that COQ6 isoform c (transcript NM_182480) does not encode an active enzyme. VA can be produced in the liver by the oxidation of vanillin, a nontoxic compound commonly used as a food additive, and crosses the blood-brain barrier. These characteristics make it a promising compound for the treatment of patients with CoQ deficiency due to COQ6 mutations.